ChemInform Abstract: An Efficient, Practical, and Enantioselective Method for Synthesis of Homoallenylamides Catalyzed by an Aminoalcohol‐Derived, Boron‐Based Catalyst. Issue 39 (23rd September 2014) - Wu, Hao; Haeffner, Fredrik; Hoveyda, Amir H.
Abstract The first general enantioselective allenyl addition to a range of aromatic and aliphatic aldehyde derived imines is presented.